Differential crosstalk between toxin-immunity protein homologs divides Myxococcus nonself siblings into close and distant social relatives - Feng Wang; Jing Luo; Zheng Zhang; Ya Liu; Duo hong Sheng; Li Zhuo; Yue-zhong Li (mBio)
ABSTRACT Many bacteria discriminate self and nonself using toxins and their corresponding immunity proteins. The toxin–immunity systems often include homologs, potentially creating crosstalk with unknown influences on kin discrimination. In this study, we investigated the kinship controlled by four homologous toxin–immunity systems in the social bacterium Myxococcus xanthus. We determined that the four homologous systems each play an independent role in the discrimination of self and nonself. However, the immunity proteins inactivate not only the corresponding nuclease toxin proteins but also some non-corresponding toxin proteins, depending on their sequence and structural similarities. The nonself relatives controlled by toxin–immunity proteins with or without crosstalk exhibit differential co-growth and collaborative behaviors. We concluded that differential crosstalk between toxin–immunity protein homologs can divide bacterial nonself lineages into close and distant relatives displaying differential collaboration and antagonistic behaviors.IMPORTANCEThis study significantly contributes to our knowledge of kin selection and social behavior in bacteria. The interactions between four homologous toxin–immunity protein systems of Myxococcus xanthus were investigated, and evidence was obtained that these systems can distinguish between self and nonself cells within a species. Importantly, this study revealed that nonself lineages, which display varying degrees of genetic relatedness, can co-grow and collaborate in distinct patterns. This discovery implies that the differential crosstalk between homologous toxin–immunity proteins can mimic the degree of kinship; through this activity, bacteria can differentiate close and distant relatives. This novel insight into bacterial social dynamics and kin discrimination supports kin selection theory and enriches our knowledge on microbial interactions and evolutionary strategies. These findings have broad implications for microbial ecology, evolution, and the development of cooperation strategies.